Recent developments in the study of failure of solid biomaterials and bone: 'Fracture' and 'pre-fracture' toughness - Zioupos, Peter (Elsevier, 1999)
Our understanding of the stress and energy requirements for the fracture of solid bio(logical)-materials has improved lately as a result of a number of investigations which highlighted some important new aspects of the failure process. The present short review article shows that under normal circumstances structural ‘damage’ precedes the creation of a fatal macrocrack and the onset of ‘failure’. The externally perceived material ‘toughness’ is a function of both: (i) the degree of prefailure accumulation of damage and (ii) of the properties of the final fracture surface. These two situations can be distinguished as ‘pre-fracture’ toughness and ‘fracture toughness’ and the relative contribution of each one in the overall toughness of the tissue is crucial for the final outcome of the failure process. Inevitably, materials which show remarkable toughness have to enhance their performance with respect to both the previous two defined quantities.
Keywords: Biomaterial(s); Bone(s); Damage; Fracture